Ragam Strategi Pengenalan Pendidikan Seks Bagi Anak Usia Dini - M.Pd., Rendy Setyowahyudi; Leda, Rosalia (Yayasan Arrahman Nahdlatul Wathan, 2023)
Sex education in early childhood needs to be introduced with the right strategy. The purpose of this research is to find out what are the strategies that can be used to introduce sex education in early childhood. The type of research used is a type of library research. Source of data obtained from 11 journal articles. The data analysis technique uses content analysis by analyzing the contents of a data message. The research was carried out within 2 months, from April to May 2023. In April the focus was to collect supporting data sources, especially regarding strategies for introducing sex education in early childhood. Then in May the focus is on compiling data in the form of research results from the various sources that have been obtained. The results obtained are that there are five strategies that can be used to introduce sex education to early childhood, namely the use of picture story books, the underwear rules program, various games, various learning methods and toilet training.